2008
DOI: 10.2174/1874364100802010037
|View full text |Cite
|
Sign up to set email alerts
|

Is Age-Related Macular Degeneration Associated with Stroke Among Elderly Americans?§

Abstract: Objective:To investigate whether age-related macular degeneration (AMD) is associated with the development of ischemic and hemorrhagic stroke among elderly Americans.Design:Population-based cohort study.Participants:The five percent random sample of 2000-2003 Medicare enrollees was obtained. The cohort (n=1,519,086) consisted of enrollees who were aged 65 or older at the first two-year (January 1, 2000 to December 31, 2001).Methods:Baseline demographic variables and chronic conditions (AMD and type, history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…7 Only 1 study divided stroke into subtypes and found that the risks of both cerebral infarction and intracerebral hemorrhage were increased in people with either neovascular or nonneovascular AMD. 8 However, a limitation of the study was that the classification of stroke and AMD were both based on medical reimbursement claims and therefore vulnerable to misclassification. Because the studies conducted so far were heterogeneous with respect to exposure categories and outcome definitions, results are not easily comparable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Only 1 study divided stroke into subtypes and found that the risks of both cerebral infarction and intracerebral hemorrhage were increased in people with either neovascular or nonneovascular AMD. 8 However, a limitation of the study was that the classification of stroke and AMD were both based on medical reimbursement claims and therefore vulnerable to misclassification. Because the studies conducted so far were heterogeneous with respect to exposure categories and outcome definitions, results are not easily comparable.…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous studies that investigated the association between AMD and stroke reported inconsistent results. [7][8][9][10][11] Most studies did not distinguish between early and late AMD nor did they subdivide late AMD into dry (atrophic) or wet (neovascular) AMD. Besides, except for a study based on medical reimbursement claims, no previous study presented separate associations for the subtypes cerebral infarction and intracerebral hemorrhage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings have been reported from a survey of 1.4 million Medicare enrollees, which found 20% to 30% higher 2-year risk of stroke among patients with neovascular AMD as compared with control subjects. 6 In the current issue of Stroke, Hu and colleagues further report on this association. 8 Using a national linkage database in Taiwan, the authors showed that patients with a neovascular AMD diagnosis had a 2-fold higher incidence of stroke than those without AMD (18.2% versus 9.9%), and this association persisted while controlling for concomitant vascular risk factors.…”
mentioning
confidence: 92%
“…12 Two reports based on US Medicare data showed inconsistent results. Liao et al reported that neovascular AMD was associated with higher adjusted 2-year incidence of stroke (8.15% versus 6.35%; OR 1.31, 95% CIϭ1.26 to 1.36), 13 but Alexander et al reported that Medicare beneficiaries with neovascular AMD had an annual rate of inpatient ischemic stroke similar to that of matched control subjects (3.5% versus 3.6%). 11 Based on a representative database and sufficient neovascular AMD case numbers (Nϭ209), our results are compatible with most previous reports, supporting an association between neovascular AMD and a higher incidence of stroke.…”
Section: Discussionmentioning
confidence: 99%